Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1590/1983-21252020v33n230rc
|View full text |Cite
|
Sign up to set email alerts
|

Univariate and Multivariate Approaches in the Characterization of Lima Bean Genotypes

Abstract: ABSTRACT To estimate the genetic diversity among the genotypes of a germplasm collection, a combined analysis of qualitative and quantitative variables was performed. The objective was to promote the morpho-agronomic characterization and estimate the genetic diversity of lima bean genotypes belonging to the Phaseolus Germplasm Bank of UFPI through univariate and multivariate approaches. The experiment was conducted on a screen house between January and September 2016, using a completely randomized desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
(13 reference statements)
0
8
0
Order By: Relevance
“…Previous studies have revealed that the use of multivariate methods is important to estimate the diversity of lima bean germplasm (GONÇALVES et al, 2019;BRITO et al, 2020). Brito et al (2020) used morphoagronomic traits to characterize eleven genotypes of lima bean from Ceará state, Northeastern Brazil, and found five clusters by using UPGMA method. Earlier, Gonçalves et al (2019) evaluated eight lima bean genotypes and found three divergent groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have revealed that the use of multivariate methods is important to estimate the diversity of lima bean germplasm (GONÇALVES et al, 2019;BRITO et al, 2020). Brito et al (2020) used morphoagronomic traits to characterize eleven genotypes of lima bean from Ceará state, Northeastern Brazil, and found five clusters by using UPGMA method. Earlier, Gonçalves et al (2019) evaluated eight lima bean genotypes and found three divergent groups.…”
Section: Resultsmentioning
confidence: 99%
“…UPGMA cluster analysis determined by Sneath and Sokal (1973) seeks to genetically discriminate individuals and allows them to be separated into groups by analyzing a set of characteristics inherent to each individual, so that there is homogeneity within the group and heterogeneity between groups (ROSA et al, 2019). Studies using the UPGMA method were carried out to identify variability among accessions of lima beans (GUIMARÃES et al, 2007;BRITO et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Lima bean (Phaseolus lunatus L.), from the Fabaceae family and native to Central America, is widely distributed in South America, whose cultivation has been intensifying in recent years (Brito, Silva, Matos, Ferreira-Gomes, & Lopes 2020). In Brazil, the main producing region is the Northeast, with 20,196 ha, which has the state of Paraíba as the largest producer, where its cultivation has been highlighted in the Agreste region, with greater production (Instituto Brasileiro de Geografia e Estatística [IBGE], 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Such as the common bean, the lima bean is characterized by the great variety diversities, depending on the place of cultivation, origin, environmental and climatic conditions (Crépon et al, 2010;Brito et al, 2020). Among the main varieties in the Northeast, Orelha de Vó stands out for its Semina: Ciênc.…”
Section: Introductionmentioning
confidence: 99%
“…Considering the socioeconomic importance of the Lima bean and the fact that high temperatures during flowering and pod development stages result in lower yields in corelated species (BRITO et al, 2020;MORAES, 2017), there is a need to select superior genotypes that can be used in crosses to obtain high-yielding and high-temperature tolerant cultivars. Under these conditions, the use of multivariate algorithms is an excellent strategy to quantify dissimilarity between individuals based on morphoagronomic and phenological traits.…”
Section: Introductionmentioning
confidence: 99%